Curating transformation can strengthen adaptation and minimize losses and damages - Joanne Clarke; Anne Haour; Hana Morel; Johanna Forster; Ben Orlove; Cornelius Holtorf; Andy Hutcheson; Victoria Aryee Adinorkuor; Christa Brunnschweiler; Nick Brooks; Sarah Wade; Nii-Adziri Wellington; et al. (npj Climate Action)
Heritage conservation recognizes that losses and damages cannot be entirely prevented, that decisions about what to keep and what to let go are fundamental to maintaining values for future generations; even when what is valued is gone. The heritage principle of curating transformation can advance climate action through pragmatic and participatory management of losses and damages, offering lessons for climate change adaptation and giving people agency over what is lost.